Urdu Translation and the Validation of a 14-Item Measure to Assess Stress Management Skills in Healthcare Workers: Measurement Invariance Across Gender - Ali, Yumna; Farhana Kazmi, Syeda (ETHICS IN PROGRESS, 2023)
This study aims to conduct an Urdu translation and a validation of the ISBF Stress Management Skills Scale in two distinct phases. The first phase includes the forward-back translation method for ISBF. The second phase includes cross validation and the establishment of psychometric properties for the ISBF scale. A sample of 500 adults working in health care was taken from different hospitals and dispensaries. The first phase of the study includes the forward-back translation method. The second phase includes exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) with invariance measurement. The total reliability of the scale is reported to be .812. EFA revealed a two-factor structure for ISBF scale, with configural, metric and scalar invariance across males and females, and comparable latent mean scores for males and females. CFA showed goodness-of fit indices for the two factors. The scale showed good internal consistency values. The model fit value includes the value for the goodness of fit index, which was .979, for the adjusted goodness-of fit index: .961, for the comparative fit index: .993, for the incremental fit index: .993, and for the root mean square error of approximation (RMSEA) value: .033. Good values of composite reliability and convergent validity were measured for both dimensions of the scale. The scale shows that this diagnostic tool can help to assess the skills used to manage stress. For criterion validity, the coping Inventory for Stressful Situations (CISS-21) was used, which showed positive correlations. The subscale of stress management was taken from the Health Promoting Life Style Profile II (HPLP-II), which also showed positive correlations. Significant mean differences were found between scores of healthcare workers with stress management skills and with those without stress management skills. The group of mean differences indicated the females have greater stress management skills as compared to men. The Urdu translated and validated instrument will be helpful in understanding behavior in healthcare settings.